Are Accommodations for English Learners on State Accountability Assessments Evidence‐Based? A Multistudy Systematic Review and Meta‐Analysis. Issue 4 (9th May 2020) - Rios, Joseph A.; Ihlenfeldt, Samuel D.; Chavez, Carlos
Abstract: The objectives of this two‐part study were to: (a) investigate English learner (EL) accommodation practices on state accountability assessments of reading/English language arts and mathematics in grades 3–8, and (b) conduct a meta‐analysis of EL accommodation effectiveness on improving test performance. Across all distinct testing programs, we found that at least one EL test accommodation was provided for both test content areas. The most popular accommodations provided were supplying students with word‐to‐word dual language dictionaries, reading aloud test directions and items in English, and allowing flexible time/scheduling. However, we found minimal evidence that testing programs provide practitioners with recommendations on how to assign relevant accommodations to EL test takers' English proficiency level. To evaluate whether accommodations used in practice are supported with evidence of their effectiveness, a meta‐analysis was conducted. On average, across 26 studies and 95 effect sizes ( N = 11, 069), accommodations improved test performance by .16 standard deviations. Both test content and sampling design were found to moderate accommodation effectiveness; however, none of the accommodations investigated were found to have intervention effects that were statistically different from zero. Overall, these results suggest that currently employed EL test accommodations lack evidence of their effectiveness.